(untitled) (Dhaka University Journal of Science, 2018)
Sitakund anticlinal structure exposes about 1.5 km of Surma group sediments and has been chosen for a comprehensive study of the mudrocks depositional environment based on sedimentological and palynological evidences. Five mudrock facies have been identified in this region. They are Mudstone Dominated, Sand/Silt Streaked Shale, Fissile Shale, Laminated Shale and Lenticular Bedded Shale. The palynological assemblages from these samples have been analyzed qualitatively, and a variety of pollen, spores, algae and fungi identified. The pollen and spores have been attributed to parent plants located at the immediate and more regional surrounding areas during the deposition of these sediments. Palynological assemblages incorporates ample of Palmae grains such as spores in the Palmipollenites and Proxaperites and predominance of pteridophytic spores. The occurrences and abundances of these pollens indicate that the deposition of the Surma mudrocks took place at the proximity of the shore level. Coastal fluvial environment is also triumphed after the previous depositional event which is apparent by the occurrence of palynomorphs of pteridophytes, angiosperms and algal origin. Dhaka Univ. J. Sci. 66(1): 37-42, 2018 (January)